Can intentions spoil the kindness of a gift? - An experimental study - Christina Strassmair (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
Consider a situation where person A undertakes a costly action that benefits person B. This behavior seems altruistic. However, if A expects a reward in return from B, then A's action may be motivated by the expected rewards rather than by pure altruism. The question we address in this experimental study is how B reacts to the intentions of A. We vary the probability, with which the second mover in a trust game can reciprocate, and analyze effects on second mover behavior. Our results suggest that the perceived kindness and its rewards are not spoiled by expected rewards.
urn:nbn:de:bvb:19-epub-10351-3
Keywords: D02; C91; D64; 330; social preferences; intentions; beliefs; psychological game theory; experiment; Soziale Beziehungen; Erwartungstheorie; Austauschtheorie (Soziologie); Sozialpsychologie; Test